Composition and functionality of the intrahepatic innate lymphoid cell‐compartment in human nonfibrotic and fibrotic livers. Issue 8 (11th July 2017) - Forkel, Marianne; Berglin, Lena; Kekäläinen, Eliisa; Carlsson, Adrian; Svedin, Emma; Michaëlsson, Jakob; Nagasawa, Maho; Erjefält, Jonas S; Mori, Michiko; Flodström‐Tullberg, Malin; Bergquist, Annika; Ljunggren, Hans‐Gustaf; et al.
Abstract : The distribution and phenotype of the ILC subsets showed specific patterns in the human fetal vs. adult liver. The composition of ILCs was altered in fibrotic livers and the frequency of ILC2s correlated with the severity of liver fibrosis. Abstract : Human innate lymphoid cells have been described to exist in different organs, with functional deregulation of these cells contributing to several disease states. Here, we performed the first detailed characterization of the phenotype, tissue‐residency properties, and functionality of ILC1s, ILC2s, and ILC3s in the human adult and fetal liver. In addition, we investigated changes in the ILC compartment in liver fibrosis. A unique composition of tissue‐resident ILCs was observed in nonfibrotic livers as compared with that in mucosal tissues, with NKp44 − ILC3s accounting for the majority of total intrahepatic ILCs. The frequency of ILC2s, representing a small fraction of ILCs in nonfibrotic livers, increased in liver fibrosis and correlated directly with the severity of the disease. Notably, intrahepatic ILC2s secreted the profibrotic cytokine IL‐13 when exposed to IL‐33 and thymic stromal lymphopoetin (TSLP); these cytokines were produced by hepatocytes, hepatic stellate cells (HSCs), and Kupffer cells in response to TLR‐3 stimulation. In summary, the present results provide the first detailed characterization of intrahepatic ILCs in human adult and fetal liver. The results indicate a role for ILC2s in human liver fibrosis, implying that targeting ILC2s might be a novel therapeutic strategy for its treatment.